2021
DOI: 10.3390/jcm10020336
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Back Optic Zone Diameter in Myopia Control with Orthokeratology Lenses

Abstract: We compared the efficacy of controlling the annual increase in axial length (AL) in myopic Caucasian children based on two parameters: the back optic zone diameter (BOZD) of the orthokeratology (OK) lens and plus power ring diameter (PPRD) or mid-peripheral annular ring of corneal steepening. Data from 71 myopic patients (mean age, 13.34 ± 1.38 years; range, 10–15 years; 64% male) corrected with different BOZD OK lenses (DRL, Precilens) were collected retrospectively from a Spanish optometric clinic. The sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 59 publications
7
64
1
Order By: Relevance
“…A recent study showed that a smaller back optic zone diameter for the OK lens would produce a smaller plus power ring diameter on the cornea's front surface. When the plus power ring's horizontal sector was inside the pupil, the mean AL elongation of those subjects was 76% lesser than the subjects who had the plus power ring outside the pupil (Paune et al, 2021). Our study supported this result and found a linear correlation between AL elongation and the amount of Half_x inside the pupil.…”
Section: Discussionsupporting
confidence: 83%
“…A recent study showed that a smaller back optic zone diameter for the OK lens would produce a smaller plus power ring diameter on the cornea's front surface. When the plus power ring's horizontal sector was inside the pupil, the mean AL elongation of those subjects was 76% lesser than the subjects who had the plus power ring outside the pupil (Paune et al, 2021). Our study supported this result and found a linear correlation between AL elongation and the amount of Half_x inside the pupil.…”
Section: Discussionsupporting
confidence: 83%
“…Further, changes described here may be specific to the BE lens design and corneal changes may be different for lenses of other designs, particularly in relation to the reverse curve parameters and back optic zone diameter. Recent studies have also demonstrated reduced orthokeratology lens back optic diameters can decrease treatment zone diameters 40 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“…A short-term study of different compression factors found that no significant changes in eye parameters were found between the different design lenses [ 28 ]. However, OK lens of smaller back optic zone diameter achieved better curative effect [ 29 , 30 ]. Further investigations will be need to make OK lens more effective in myopia control.…”
Section: Discussionmentioning
confidence: 99%